To expand the expression \(-\frac{7}{6}(3g + 2)\), you can distribute \(-\frac{7}{6}\) to both terms inside the parentheses:
\[ -\frac{7}{6}(3g) + -\frac{7}{6}(2) \]
Now, calculate each term:
-
For the first term: \[ -\frac{7}{6}(3g) = -\frac{21}{6}g = -\frac{7}{2}g \]
-
For the second term: \[ -\frac{7}{6}(2) = -\frac{14}{6} = -\frac{7}{3} \]
Now, combining these results gives us:
\[ -\frac{7}{2}g - \frac{7}{3} \]
So the final expanded expression is:
\[ -\frac{7}{2}g - \frac{7}{3} \]
This corresponds to the response:
\(-\frac{7}{2}g - \frac{7}{3}\)